Metallic materials properties development and standardization (MMPDS) : MMPDS-07, April 2012. (Federal Aviation Administration ; Battelle Memorial Institute [distributor], 2012)
"MMPDS-07 supersedes MMPDS-06 and prior editions of the MMPDS as well as all editions of MIL-HDBK-5, Metallic materials and elemets for aerospace vehicle structures handbook that was maintained by the U.S. Air Force. The last edition, MIL-HDBK-5J, was cancelled by the U.S. Air Force in March 2006. This document contains design information on the mechanical and physical properties of metallic materials and joints commonly used in aircraft and aerospace vehicle structures. All information contained in this Handbook has been reviewed and approved using a standardized process. The development and ongoing maintenance process involves certifying agencies, including the FAA, DoD, and NASA, and major material suppliers and material users worldwide."--Page i.